Left-Handed Theology and Inclusiveness - Jensen, Gordon A. (Horizons, 1990)
In the concern for inclusiveness, one area that has been largely neglected is the discrimination against left-handedness. This paper looks briefly at some of the scriptural and social stigmas and implications attached to left-handedness. Using Luther's theology of the cross as its basis, a left-handed theology is introduced. Arguing for the need for a theology which focuses on those who are marginalized, a left-handed theology offers a model whereby God's left hand offers to those who are in "minority" positions grace and solidarity. This is contrasted to the right hand of God, which portrays a God of power, strength, and triumphalism. The hand of God which one chooses to relate to determines, then, how one does theology, and how a theological inclusiveness is developed.